ENTITAS KERIFAN TRADISI LOKAL HOPONG PADA MAKNA SIMBOL RITUAL DALAM MEMPERKUAT CINTA BUDAYA MASYARAKAT DAYAK UUD DANUM DI DESA PANEKASAN KECAMATAN SERAWAI - Fusnika, Fusnika; Hartini, Agnesia; Gilang, Aldisius (STKIP Persada Khatulistiwa Sintang, 2023)
The background of this research problem is regarding the processes in the hopong tradition and the values contained in the hopong. The traditional hopong ceremony is believed by the community as an ancestral heritage that has meaning, certain values and functions. This research was conducted in Panekasan Village, Serawai District, Sintang District. The purpose of this research is to describe clearly the local hopong traditional entity in the meaning of ritual symbols to strengthen cultural love for the Dayak Uud Danum community in Panekasan Village, Serawai District. The method used is ethnographic qualitative research. The results of this study are that the local hopong tradition entity in the Uud Danum Dayak community is a tradition that is still often carried out by the community. The values contained in the hopong tradition include social values, entertainment values, moral values, aesthetic values, and belief or religious values. The conclusion in this study is that the culture of hopong is a culture inherited from the ancestors of the Dayak Uud Danum tribe and can strengthen love for culture and preserve the customs of hopong in Panekesan Village, Serawai District.Â Keywords: Entities, Hopong local traditions, Ritual Symbols, Love Culture, Dayak UUD Danum